Non Integer Identification of Rotor Skin Effect in Induction Machines - Abdelhamid Jalloul; Khaled Jelassi; Jean-Claude Trigeassou (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Fractional identification of rotor skin effect in induction machines is presented in this paper. Park‘s transformation is used to obtain a system of differential equations which allows to include the skin effect in the rotor bars of asynchronous machines. A transfer function with a fractional derivative order has been selected to represent the admittance of the bar by the help of a non integer integrator which is approximated by a J+1 dimensional modal system. The machine parameters are estimated by an output-error technique using a non linear iterative optimization algorithm. Experimental results show the performance of the modal approach for modeling and identification.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2286